DISIPLIN KERJA DALAM PENINGKATAN KINERJA PELAYANAN PUBLIK - Putri, Ni Kadek Ayu Wulan Widiantari; Dewi, Ni Luh Sinar Ayu Ratna; Aryawati, Ni Putu Ari (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
The performance of public services is essentially used as an evaluation of the succes or failure of the implementation of service activities, service procedures and policies in accordance with predetermined goals by increasing work discipline can direct the attitudes, behavior and actions of service providers to be better. In accordance with applicable rules and procedures in achieving company goals. This study aims to analyze the obstacles in improving work discipline, the efforts made to improve work discipline, and work discipline in improving public service performance at the Mataram SAMSAT Office. The theory used in this study is McClelland's theory of motivation and performance theory. The method used in this study is a qualitative method which is described in detail through observation and interviews with informants. The results of the study show that there are several obstacles in improving employee work discipline, namely there are still employees who arrive late, employees return before the set time, lack of employee self-awareness and efforts to increase work discipline in public service performance have not been fully implemented properly, it can be seen through indicators work discipline, namely: (1) time discipline, (2) regulatory discipline, (3) responsibility discipline, and work discipline in improving public service performance that has not been fully implemented properly can be seen through public service performance indicators, namely: (1) productivity, (2) quality of service, (3) responsiveness, (4) accountability.